The Effect of Rode Learning Model on Enhancing Students Communication Skills - Arief Ertha Kusuma; Wasis; Endang Susantini; Rusmansyah (Indonesia Approach Education, 2022)
Communication skills in physics learning are essential to life talents that can be used to solve problems in everyday life. The Read Outline Discussion Evaluation (RODE) model is a learning tool designed to help students improve their communication skills. This research was conducted in the Elementary School Teacher Study Program with Basic Science 2nd material and involved 100 students. This study focuses on improving students' writing communication skills before and after the teaching process with the RODE learning model to determine the effectiveness of the RODE learning model. This study used one group pretest-posttest design (O1-x-O2). Before being applied to the RODE learning model, the average score of the indicators of students' written communication skills was at a low level (1, 24), and it had a score of 3.68 (high level) after the RODE learning model was implemented. This result shows that the RODE model significantly impacts students' written communication skills in the high category for both classes. In addition, students' written communication skills improved in the high category, N-gain significantly increased in the high criteria, and consistent N-gain was observed in the Elementary School Teacher Study Program.